Digitalisasi perbankan Syariah: Tantangan dalam menjaga keamanan data pribadi nasabah - Fakhrezy, Moh Zaky (Maliki Interdisciplinary Journal, 2024)
This study examines the challenges faced by Islamic banking in maintaining the security of customers’ personal data in the era of digitalization. This research aims to analyze various threats related to customer personal data leakage due to the digitalization of banking services, as well as efforts made by Islamic banks to mitigate these risks. A case study was conducted on Islamic banks in Indonesia using a qualitative approach. The findings show that the main data security threats include cyberattacks, employee negligence, and data mismanagement by banks. For this reason, Islamic banks need to implement various data security policies and technologies, as well as conduct socialization to customers. This aims to maintain customer trust and ensure compliance with personal data protection regulations.